1994
DOI: 10.1007/bf00335073
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric head trauma: influence of age and sex

Abstract: A consecutive unselected series of 1812 children (up to 15 years old) admitted for head injuries over a period of 8.5 years was studied. The cases were divided up according to five categories of pathology: benign injury, extradural haematoma, subdural haematoma, open brain laceration and brain contusion in a broad sense. All cases of benign injury were from the Geneva area (57000 children) and 52% of the cases of severe injury were referred from other places. To these 1812 cases were added those of 23 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 19 publications
3
20
2
Order By: Relevance
“…Many other authors have found a higher mortality rate in younger children (33, 50 -55), whereas only a few have shown no effect of age or lower mortality rate in infants (34,49). Reasons postulated for higher mortality rates in infants have included the more compliant skull as well as the higher incidence of nonaccidental trauma in this age group.…”
Section: Discussionmentioning
confidence: 84%
“…Many other authors have found a higher mortality rate in younger children (33, 50 -55), whereas only a few have shown no effect of age or lower mortality rate in infants (34,49). Reasons postulated for higher mortality rates in infants have included the more compliant skull as well as the higher incidence of nonaccidental trauma in this age group.…”
Section: Discussionmentioning
confidence: 84%
“…This study of post-traumatic intracranial hematomas in infancy reveals that age and sex are closely related to the type and mechanism of injury causing CCT and to the probability of developing post-traumatic ICH, since girls showed a higher frequency among children under 3 years of age, and boys among those over 7 years of age [2,3,19]. Of the total population in this study, 73.5% were boys, coinciding with data published by other authors [4].…”
Section: Discussionmentioning
confidence: 87%
“…The majority of head injuries in childhood are not severe and have minor consequences. When the head injury is severe, however, the sequelae are important and reflect a high mortality rate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).5%) [1,2,4,5,9,14,15,24,27]. Analysis of the epidemiological aspects in this group of patients is important, since work in this field will contribute to the prevention of such injuries and a reduction in the number of cases.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of children under the age of 2 yr, who have open anterior fontanelle and lack communication skills, previous studies have shown different mechanisms and clinical features, compared with children over the age of two (29, 30). Accordingly, there are several items that should be added in the examination of infants.…”
Section: Discussionmentioning
confidence: 98%